THE CONDITIONALITY OF HUMAN MATURATION BY SOCIAL FACTORS IN THE CONCEPT OF THE SOUL BY ALFRED ADLER (Scientific journal of the Fergana State University, 2024)
The article examines the issue of human development conditioned by social factors in Alfred Adler's concept of the soul. The views of the thinker on the issues of the opening of human creative potential as a result of the origin of selfless human, ethical relations are described.